Cyber Da’wa of “Aa Gym Daily Vlog” as Moslem Moderate Preaching Medium - Supratman, Lucy Pujasari; Wahyudin , Aep (Proceedings of International Conference on Da'wa and Communication, 2020)
New media plays a big role in virtual da’wa for society in a disruption era. "Aa Gym Daily Vlog" which released on July 29, 2020, is one of the digital media video blog platforms that received 6.44K subscribers within only one week of releasing its first teaser vlog. The vlog video content is posted each Monday and Thursday every week. The research purpose is to describe the virtual da’wa message packaging by using an Islamic preacher personal blog. The writer used a qualitative method with a discourse analysis approach. Data collection was done through observing 17 scenes of "Aa Gym Daily Vlog" premiere vlog content. This virtual da’wa of "Aa Gym Daily Vlog" is packaged in a concise and brief based on Aa Gym daily activities who carried out manners, morals, and the science of tauhid in accordance with the guidance of Rasulullah saw. The use of virtual da’wa "Aa Gym Daily Vlog" offers easy access to mad’u (da’wa recipients) directly in real action. The da’wa messages in "Aa Gym Daily Vlog" content are made very applicable, starting from the daily activities of Aa Gym about waking up and the traditions of the prophet Muhammad saw in social daily life. Virtual da’wa of Aa Gym's is made seriously and professionally as an effort to encourage the digital community in developing themselves based on Islamic guidance.